Tempering and Annealing in a Verdier-Stockmayer Polymer - Obias, E. R.; Banzon, R. S. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Two Monte Carlo methods, simulated annealing and parallel tempering, were applied to a Verdier-Stockmayer polymer. The efficiency of the two algorithms in exploring the lowest energy state possible for the model polymers was measured by the number of energy-degenerate configurations (configurations that have the same energy but are structurally different). Parallel tempering consistently explored more energy-degenerate configurations as compared with simulated annealing.